O controle concorrencial das condutas unilaterais das empresas estatais - Afonso, Marjorie Gressler (2017)
In this paper, we intend to study how CADE carries out antitrust control of unilateral conduct of state-owned enterprises. We intend to verify: (i) whether state-owned enterprises are subject to the antitrust control by CADE, as provided for in Law 12,529 of 2011 (ii) whether CADE exercises this control, (iii) whether and in what cases, there should be an exemption from competitive control of unilateral conduct of state-owned enterprises, and (iv) whether the methodology adopted by CADE for the analysis and control of unilateral conduct by state-owned is adequate to identify and restrain unilateral anticompetitive practices by these companies. In the first part, we examine the rules that define CADE's competence in order to define the subjective scope of Law 12,529 of 2011 and analyze some precedents in which CADE addresses its subjective competence with special emphasis on the application of the competition rules to public entities and public services. We have verified that CADE is indeed competent to control the competitive behavior of state-owned enterprises but has used this power only on rare occasions. Next, we examined the possible competitive exemptions that may apply to companies in general, and to state-owned enterprises, specifically. We have verified that jurisprudence and legal scholars already recognize that regulation may lead to imunity from antitrust control. Furthermore, we addressed if measures taken by of state-owned enterprises that are to promote public policies could be exempted from antitrust control. In the second part, we present some incentives that apply to shareholders and administrators of state-owned enterprises and that will affect the competitive behavior by these firms. Next, we analyzed CADE’s methodology for the identification and control of unliteral anticompetitive conduct – specifically regarding the abuse of dominant position and predatory pricing – to verify if it is adequate when applied to state-owned enterprises. We have verified that the rule of reason applied to verify if the conduct of a dominant firm is abusive, in general, only considers the economic efficiencies of the investigated conduct, and not other possible social and public policies gains that can be legitimately pursued by the state-owned enterprises